The structural relationship between nutrition, cognitive and non-cognitive skills: evidence from four developing countries - Sanchez, A (Young Lives, 2013)
Both cognitive and non-cognitive skills are rewarded in the labour market. However there is little evidence about how these abilities are formed in the context of developing countries. I study the way in which cognitive and non-cognitive skills are simultaneously acquired in the transition from childhood to adolescence using longitudinal data from four countries: Peru, India, Vietnam and Ethiopia. I estimate a linearized version of the technology of skills formation, linking inputs observed at 7 to 8 years to outputs observed at 11 to 12 and 14 to 15 years. I find evidence of self-productivity mainly for cognitive skills and cross-productivity for both types of skills. I then extend the technology of skills formation to account for the role of nutritional status in the acquisition of skills. Height-for-age is found to be a relevant input in the skills formation model, having a direct as well as an indirect effect on skills accumulation. To obtain estimates of the long-term impact of nutritional investments during the early childhood period on later abilities, I use evidence gathered from a second model that links early height-for-age to cognitive ability at 7 to 8 years. Linking results from both models, I find that an increase of 1 standard deviation in early height-for-age tends to increase cognitive skills during adolescence by 6%, 9%, 17% and 7% in Peru, India, Vietnam and Ethiopia, respectively. It also increases non-cognitive skills by 2% and 4% in India and Vietnam, respectively.